2021
DOI: 10.1088/1755-1315/936/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric phase delay correction of PS-InSAR to Monitor Land Subsidence in Surabaya

Abstract: Atmospheric phase delay is one of the most significant errors limiting the accuracy of Interferometric Synthetic Aperture Radar (InSAR) results. In this research, we used the Generic Atmospheric Correction Online Service for InSAR (GACOS) data to correct the tropospheric delay modeling from the persistent scatterers’ InSAR monitoring. Eighty-one (81) Sentinel-1A images and tropospheric delay maps from GACOS monitored land subsidence in Surabaya city between 2017 and 2019. InSAR processing was carried out using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The subsidence value of the observation point in this area has a significant value compared to the land subsidence that occurred in the eastern or southern regions. These results are in agreement with the studies by Ulma et al [7] that monitoring land subsidence by PS-InSAR. In terms of geology, subsidence occurs in alluvial areas which are still undergoing a process of compaction and consolidation.…”
Section: Figure 2 Velocity Rate Of Surabayasupporting
confidence: 94%
“…The subsidence value of the observation point in this area has a significant value compared to the land subsidence that occurred in the eastern or southern regions. These results are in agreement with the studies by Ulma et al [7] that monitoring land subsidence by PS-InSAR. In terms of geology, subsidence occurs in alluvial areas which are still undergoing a process of compaction and consolidation.…”
Section: Figure 2 Velocity Rate Of Surabayasupporting
confidence: 94%
“…Thus, an effective GACOS correction can help reduce the influence of tropospheric impacts on the study area. However, the accuracy of the turbulence recordings within the GACOS product determines the potential correction effect [4].…”
Section: Resultsmentioning
confidence: 99%
“…Multi-Temporal Interferometric SAR (MT-InSAR) analysis technique can provide spatially continuous measurements of the ground deformation [2] and monitoring of tectonic-induced geological phenomena [3]. Several researchers use the geodetic method, such as the implementation of the InSAR technique as already done by Ulma et al [4], Ayani et al [5], and the GNSS technique by Anjasmara et al [6] to detect ground deformation 1127 (2023) 012007 IOP Publishing doi:10.1088/1755-1315/1127/1/012007 2 by only taking a case study from one of the cities, Surabaya, traversed by the Kendeng Fault. In contrast, each segment of the Kendeng Fault has a different and complex geological structure.…”
Section: Introductionmentioning
confidence: 99%
“…The results of [27] also indicated that InSAR-derived land deformation data on a monthly scale could be used for characterization of the hydraulic head and aquifer properties in con ned aquifer systems, even those experiencing signi cant subsidence. Although data availability has been greatly improved by Sentinel-1, there are still barriers to analysis of satellite images and has been used for different applications such as land subsidence estimation [27,40,41,42], landslide estimation [43,44], and earthquake and other deformation estimation [45,46]. The motivation for choosing GMTSAR in this paper was due to its high processing performance, C-shell scripting susceptibility, good potential for parallel implementation, and free access compared to other commercial SBAS processing systems (such as SARscape -https://l3harrisgeospatial.com and GAMMA [47]).…”
Section: Introductionmentioning
confidence: 99%